THE APLICATION OF ROLE PLAY METHOD TO INCREASE PARTICIPATION OF STUDENTS IN LEARNING MANAGEMENT OF MIDWIFERY AT DIPLOMA-III OF MIDWIFERY STUDENTS - Gita Kostania; Kuswati .; Firly Ratnawati (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: In order to improve the achievement of learning objectives, we need a method of learning which can encourage the participation of students. Role play is a learning method that can increase student participation. The aims of this study is to determine the increase of student’s participation in learning midwifery management using role-play method. Type of this research is a classroom action research, consisting of two cycles with phases: planning, implementation, observation, and reflection. There was an increase in student participation, judged by an increase in the percentage of each indicator, including student attendance for the planning of the first cycle to the second cycle of (25%), where as the planning, implementation and process of discussion (10%). In the process of implementation of role-play consists of planning and implementation, increased participation from the first cycle to the second cycle, the average amount (35%). Furthermore, motivation of the students, also increased from the first cycle to the second cycle, with an average of each indicator by (15%). Keyword: role play method, participation, midwifery students PENERAPAN METODE ROLE PLAY UNTUK MENINGKATKAN PARTISIPASI MAHASISWA DALAM PEMBELAJARAN MANAJEMEN KEBIDANAN PADA MAHASISWA DIII KEBIDANAN Abstrak: Tujuan penelitian ini adalah untuk mengetahui peningkatan partisipasi mahasiswa pada pembelajaran manajemen kebidanan dengan menggunakan metode role play. Jenis penelitian ini merupakan penelitian tindakan kelas yang terdiri atas dua siklus dengan tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Terdapat peningkatan partisipasi mahasiswa terhadap indikator kehadiran serta pelaksanaan dan diskusi. Proses pelaksanaan role play untuk masalah aktual yang berkaitan dengan mahasiswa, masalah problematik, dan pemecahan masalah terdapat peningkatan tajam (100%), juga sarana dan prasarana. Peningkatan dari siklus I ke siklus II juga meliputi persiapan naskah cerita, kecocokan pemeran efektivitas perilaku, penghayatan, dan pemeranan sesuai dialog. Selain itu, peningkatan juga terlihat pada hasil usaha untuk motivasi mahasiswa agar lebih memperhatikan, mencatat hal-hal penting, dan mau mengemukakan pendapat. Di pihak lain, mahasiswa yang hanya melamun dan sibuk sendiri mengalami penurunan. Kata Kunci: metode role play, partisipasi, manajemen kebidanan